AB0451 Incidence of opportunistic infections during rituximab, abatacept or tocilizumab treatments for rheumatoid arthritis in clinical practice. (12th June 2018) - Leon, L.; Peñuelas, M.; Candel, F.J.; Freites, D.; Rodriguez, L.; Jover, J.A.; Abasolo, L.
Abstract : Background: With the expanding use of biologic disease-modifying anti-rheumatic drugs (bDMARDs), opportunistic infections (OI) are a major concern in Rheumatology. Objectives: Our purposes were to describe and compare the incidence of OI in RA treated by non-TNF-targeted biologics. Methods: We performed a retrospective longitudinal observational study from 2007 to 2017. We included subjects followed in our outpatient clinic, diagnosed with RA according to ACR criteria, whom started treatment with a bDMARD [rituximab (RTX), abatacept (ABA), or tocilizumab (TCZ)]. According to the microbiologist criteria, we consider OI when there was a positive culture (for Virus, Fungus, bacterial or parasitary) or compatible symptoms that responded to specific treatment. Severe IO was considered if required hospitalisation. We also collected secondary variables: sociodemographic, clinical and other treatments. We used survival techniques to estimate the incidence of OI, expressed per 1000 patient-year [CI 95%]. Exposure time was defined from the start date of each bDMARDs until the development of an OI, discontinuation, loss of follow up or end of study (01/02/2017). Results: We analysed a total of 164 patients with 219 different courses of bDMARDs treatment. Of these, 76% were women with a mean age at first bDMARD of 61.4±15 years. Rheumatoid factor was positive in 73.6%. Main comorbidities were: Hypercholesterolemia (53.3%), Hypertension (53.2%), Depression (25%), Diabetes (15%), and Ischaemic Heart Disease (9.8%). VSG mean was 38±28, and the mean WBC count was 7.8±2.7. The median time from onset of RA until onset of bDMARD was 2.8 years [0.8–6.2]. Of these, 132 were on RTX, 47 were on ABA and 40 were on TCZ. There were 12 OI (9 with RTX, 2 with ABA and 1 with TCZ). RTX have 2 Fungus (Candida krusei and Klebsiella), and 7 Virus (4 Herpes Zoster, 1 virus B reactivation, 1 virus C reactivation). OI for ABA was 2 Virus (1 Herpes Zoster, 1 virus B reactivation), while we found one virus OI with TCZ Fungus (Herpes Zoster). There were no bacterial or parasitary OI. Global incidence rate of OI was 30.49 [17.3–53.6]. The incidence of OI was 38.92 [20.2–74.8] for RTX, followed by ABA with 21.61 [5.4–86.4], and TZC with 14.3 [2–101.6]. We found 3 severe OI (2 fungus infections, 1 virus B reactivation). The incidence of severe OI was 7.62 [2.4–23.6], all of them requiring hospitalisation with no deaths. Severe OI have a higher incidence for men 21.1 [5.2–84.2] than women 3.3 [0.4–23.7]. All patients with severe OI were taking corticosteroids, and at least one synthetic DMARD. TCZ did not have any severe OI, and the incidence of severe OI was 10.8 [1.5–76.7] for ABA, followed by RTX with 8.6 [2.1–34.5]. Conclusions: The incidence of OI in three non-TNF-targeted biologics in real life conditions is described. Incidence found was near 31 cases per 1000 patients -year. Virus and fungus are the OI more frequents in these bDMARDs. Doctors using bDMARDs should be concerned about this problem and be aware for the detection and management of OI. Disclosure of Interest: None declared